Pendampingan Hukum Fikih dan Pembelajaran Al Qur’an Metode Utsmani di TPQ Roudlotul Jannah Ponorogo - Fatmawati, Indah; Jihan Zahara, Aulia; Her Perdiansyah, Eka Andanni; Darin Rofifah, Khansa; Salsabila, Miyah; Rifaldy, Mohammad; Sugiyanto (Jurnal Aksi Afirmasi, 2025)
Understanding fiqh law and Qur'an education is a very important education to be taught. Fiqh punishes obligatory 'ain for everyone to study the Qur'an. Understanding the jurisprudence and education of the Qur'an is also prioritized to be taught when a human being is still in childhood. In Ponorogo itself, there are many Qur'an Education established by the Government and the private sector. Of the many existing Qur'an Educational Institutions, there are various methods applied in teaching the Qur'an to students, such as the Ummi, Ottoman and even classical methods. The success of each method used certainly depends on various factors. Meanwhile, the understanding of fiqh law can be inserted in the study of the Qur'an. In order to realize success in providing understanding and education of the Qur'an, Academicians of the Riyadlotul Mujahidin Ngabar Ponorogo Islamic Religious Institute (IAIRM Ngabar) and several students who were divided into several groups then assisted in understanding fiqh law and learning the Qur'an at TPQ Roudlotul Jannah which was located in Carangejo Village, Sampung District, Ponorogo Regency. The assistance carried out was carried out by introducing fiqh law and Ottoman methods and began by analyzing what factors were obstacles in learning fiqh law and the Qur'an in the village. The results of the mentoring have a positive impact with the increasing enthusiasm of students in learning fiqh law and Qur'anic.